The mechanical origin of the radial shape in distichous phyllotaxy grass plants. Issue 2 (15th July 2021) - Tokuyama, Yoshiki; Koide, Yohei; Onishi, Kazumitsu; Hikichi, Kiwamu; Omachi, Miku; Takamure, Itsuro; Kishima, Yuji
Abstract: Three-dimensional plant shapes are influenced by their phyllotaxy, which plays a significant role in their environmental adaptation. Grasses with distichous phyllotaxy have linearly aligned culms and usually have vertical fan-like shapes. Counterintuitively, some distichous phyllotaxy grasses have radial shapes. Here, we investigate the organ-level mechanism underlying radial shape development in the distichous phyllotactic wild rice species ( Oryza rufipogon ). Detailed time-course phenotyping and three-dimensional micro-computed tomography showed that changes in the elevation angle in the main culm and azimuth angle in the primary tillers contribute to radial shape development. To infer the mechanical basis of the shape change, we simulated the movements of culms controlled by different kinematic factors. The computational models predicted that the combination of movements, including that controlled by negative gravitropism, produces the overall radial shape. This prediction was experimentally assessed. The analysis using a near-isogenic line of the gene, PROG1 for prostrate growth and the gravitropic mutant ( lazy1 ) showed an association between genes and our model parameters. Our findings provide a simple, yet substantial, kinematic model for how the shape in distichous phyllotaxy plants changes as part of their adaptation to the surrounding environment.